2017
DOI: 10.3389/fmed.2017.00028
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the World Health Organization 2nd International Standard for Factor XI, Plasma, Human

Abstract: The 1st International Standard (IS) for blood coagulation factor XI (FXI), plasma, has been successfully used for potency labeling of FXI therapeutics and for diagnosis of FXI deficiency in patients. With stocks of the 1st IS near depletion, a replacement is required. In addition to the functional activity value, assignment of an antigen value to the 2nd IS would allow harmonization of antigen assay methods and differentiation of patients who have low functional activity but normal antigen FXI levels from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…11 In this analysis log-trans- ples, that this range is appropriate for similar functional assays. 12,13 Non-linearity was assessed by visual inspection of the plotted data, to rule out anomalously significant results due to tight replicates (and underestimation of the residual error). In other cases, invalid assays due to significant non-linearity (P < .01) were further investigated by removal of non-linear points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In this analysis log-trans- ples, that this range is appropriate for similar functional assays. 12,13 Non-linearity was assessed by visual inspection of the plotted data, to rule out anomalously significant results due to tight replicates (and underestimation of the residual error). In other cases, invalid assays due to significant non-linearity (P < .01) were further investigated by removal of non-linear points.…”
Section: Discussionmentioning
confidence: 99%
“…The strict range of 0.90 to 1.11 allows any samples with doubtful parallelism to be excluded and not bias the final relative potency estimates obtained. Several previous (larger) studies have demonstrated, through analysis of data from coded duplicate samples, that this range is appropriate for similar functional assays 12,13 . Non‐linearity was assessed by visual inspection of the plotted data, to rule out anomalously significant results due to tight replicates (and underestimation of the residual error).…”
Section: Collaborative Studymentioning
confidence: 99%
“…The candidate material (15/180) is the same as used for the second IS for FXI, Plasma, details of which have been published elsewhere ( 9 ). Briefly, plasma that had been prepared by the centrifugation of whole blood collected into CPD (citrate-phosphate-dextrose) adenine anticoagulant was purchased from the UK Blood Service.…”
Section: Methodsmentioning
confidence: 99%
“…This study was carried out alongside the study on the second IS for FXI, Plasma ( 9 ), and the participants’ laboratory number was assigned arbitrarily across the two studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation